Hyperactivity of the hypothalamo-pituitary-adrenal axis in obesity: a study of ACTH, AVP, beta-lipotrophin and cortisol responses to insulin-induced hypoglycaemia. - Weaver, J; Kopelman, P; McLoughlin, L; Forsling, M; Grossman, A (1993)
OBJECTIVE: The purpose of this study was to determine whether alterations in the hypothalamo-pituitary-adrenal axis and arginine vasopressin secretion, which have been associated with animal obesity, also occur in man. DESIGN: Cross-sectional analysis of extremely obese women and normal weight controls. PATIENTS: Thirty-three obese premenopausal, non-diabetic women (mean age 31 years, mean body mass index (BMI) 41), and 15 normal weight controls (mean age 24 years, mean BMI 22). MEASUREMENTS AND RESULTS: Arginine vasopressin (AVP), ACTH, beta-lipotrophin and cortisol responses to insulin-induced hypoglycaemia (0.2 units Actrapid/kg body weight for obese; 0.15 unit/kg for controls) were measured. The obese women were further characterized by anthropometric measurements (weight, body mass index, fat distribution) and indices of insulin secretion/resistance: fasting insulin, insulin secretion during 75-g oral glucose tolerance test area under curve, insulin-stimulated glucose disposal and an index of insulin resistance. No significant differences were found in the basal levels of ACTH, AVP, beta-lipotrophin or cortisol. An augmented peak beta-LPH (n = 16, P < 0.02, the difference of the mean 3.65, 95% confidence interval 1.33-10) and ACTH (n = 16, P = 0.05, the difference of the mean 2.12, 95% CI 1.0-4.5) response were found in obese as compared with normal weight controls. Both ACTH and AVP areas under the curve were similar in both groups studied. There was additionally a direct positive association between the integrated ACTH response (area under the curve) and the weight of the obese subjects (P < 0.05, r2 = 0.265). The cortisol response was negatively correlated with insulin-stimulated glucose disposal (P < 0.01, r2 = 0.23), but not with other indices of insulin secretion/resistance (fasting insulin, oral glucose tolerance test area under the curve, index of insulin resistance) or fat distribution. Comparable responses to hypoglycaemia were seen for AVP and cortisol. There was no correlation between the ACTH, AVP or cortisol responses. CONCLUSION: Obesity is associated with increased activity of the hypothalamo-pituitary-adrenal axis as supported by augmented ACTH and beta-lipotrophin secretion in response to insulin-induced hypoglycaemia and the positive association between the ACTH response and the body weight of obese women studied.